Prediksi Financial Distress Sebelum dan Selama Masa Pandemi Covid-19 - Kassidy, Carissa Lorenza; Handoko, Jesica (E-Jurnal Akuntansi, 2022)
This study aims to determine the differences in the predictions of financial distress before and during the pandemic. A single variable is used in the study from the calculation of the financial distress prediction model. The prediction model used in this study is the prediction model of Grover, Springate, Taffler and Zmijewski. The object of research is a manufacturing company listed on the Indonesia Stock Exchange in the 2018-2020 period. Hypothesis testing using Paired Sample T-Test. The results showed differences in the predictions of financial distress using the Springate and Taffler prediction models before and during the COVID-19 pandemic. Meanwhile, the results of predictions of financial distress with the prediction model of Grover and Zmijewski tend not to show any difference. This finding implies that the use of earnings before interest and tax ratios in the Springate model and the Taffler model is better able to predict financial distress before and during the pandemic than other models that use profit after tax indicators. Keywords: Financial Distress; Grover; Springate; Taffler; Zmijewski